The Effect of Using the powtoon Application on learning outcomes of Class XI IPA Students SMAN 1 Sidrap - Wahyuni, Sri; M, Usman; Syamsunir, Syamsunir; Hermansyah, Sam; Tang, Jusman (International Journal of Educational Narratives, 2023)
Background. This Powtoon application on the science learning outcomes of students in Class XI IPA SMA Negeri 1 Sidrap. The population is 190 students, so the sampling in this thesis is 20% of the population, meaning 190 X 20% = 38 student samples using Suharsimi Arikunto's opinion with sampling techniques, namely, percent. Purpose. There are 2 variables in this study, namely the independent variable using the Powtoon application (X) and the dependent variable, namely science learning outcomes (Y). Method. This research was conducted at SMA Negeri 1 Sidrap, precisely in Rappang Kec. Panca Rijang, Kab. Sidenreng Rappang Data collection techniques using tests and documentation. Results. The collected test results data were analyzed using descriptive techniques using the average formula (mean). Based on the results of data analysis obtained X value = 87.052> Y value = 72.842 so it can be known that there is an effect of using the Powtoon application on the science learning outcomes of students in class XI IPA SMA Negeri 1 Sidrap. Conclusion. Based on the research results obtained, it can be concluded that there is an effect of using the Powtoon application on the science learning outcomes of students in class XI IPA SMA Negeri 1 Sidrap, this shows that the working hypothesis which states that there is an effect of using the Powtoon application on the science learning outcomes of students in class XI IPA SMA Negeri 1 Sidrap, is accepted.